Clinicopathological study of lepromatous leprosy and histoid leprosy in a tertiary care institute - N, SindhuShree (Journal of Pathology of Nepal, 2021)
Background: Lepromatous leprosy is a clinical course seen in patients with inefficient cellular immunity against Mycobacterium leprae, resulting in anergy. A highly bacilliferrous type of lepromatous leprosy is histoid leprosy. Histoid leprosy was initially reported to manifest after the failure of long-term dapsone monotherapy, irregular therapy, or inadequate therapy. However, it is now well known that histoid leprosy develops de-novo as well. This study was undertaken to know the incidence and clinicopathological characteristics of lepromatous leprosy and histoid leprosy. Materials and Methods: This was a combined (both retrospective and prospective) study of lepromatous and histoid Leprosy, undertaken in the Department of Pathology, Karnataka Institute of Medical Sciences, Hubballi, over 42 months from January 2013 to June 2016. Results: Out of the 16 clinically diagnosed lepromatous leprosy cases, only 5 were histologically proven to be the same. Of the seven clinically diagnosed histoid leprosy cases, 4 were histoid leprosy on histopathology and the remaining 3 were lepromatous leprosy. All 4 patients of histoid leprosy were cases of De- Novo histoid leprosy. The commonest skin lesion encountered were erythematous patches (9/16) in lepromatous leprosy and nodules (5/7) in histoid leprosy. Conclusions: Lepromatous leprosy when diagnosed in an early stage, interrupts the epidemiological chain and avoids the associated disabilities and psychological effects for the patient and family. Histoid leprosy is a rare entity that can also present with no history of prior anti-leprosy treatment, the diagnosis of “de-novo histoid leprosy” should be kept in mind.